Carlos Lanfranco La Hoz: The End of an Era and The Beginning of a Hope - Murillo Peña, Juan (1999)
The present assay focuses on the role of the master Carlos Lanfranco La Hoz on building the cultural imaginary of our Faculty. We address his outstanding performance within the various events of our institutional history. We state that Lanfranco is the expression of a new medical culture within the San Fernando Faculty of Medicine, being himself a mandatory reference for a community in reconstruction and through the search of an identity. We address the values which led him, such as tolerance, academic excellence, humanistic vocation, as well as teaching with the aim of building a universitary community. We propose that while the Faculty becomes a community (Universitas) able to accomplish Lanfranco’s goals, we must consider him the most important reference of the second half of the century, in order to reach a new medical culture, based upon the best of our scientific and universitary tradition toward a new base of institutional culture to allow us the achievement of better development conditions at facing the XXI century.